Synthesis of Quinoline-Based Rh-Sb Complexes Inhibition of Halide Transfer to Access a Rh→Sb Z‑Type Interaction - Ou, Xinrui (Organometallics, 2025)
© 2025 The Authors. Published by American Chemical Society.